IJCM_181A: Health behavioral change and Associated factors among patients diagnosed with non-communicable diseases in the Rural areas of Southern India - Kumar C. Sunil; Chandrasekhar C.; Madhu T. (Wolters Kluwer Medknow Publications, 2024)
Background: Non-communicable diseases (NCDs) contributed to 71% of the global mortality and affect the ageing population with variable proportions. NCD diagnosis gives an opportunity for patients to change their health behaviors. Secondary prevention strategies like diet modification, physical activity and smoking cessation after NCD diagnosis are important and should be emphasized particularly for middle-aged and older adults. Objectives: 1. To assess the level of health behavioral change adopted by the patients diagnosed with NCDs registered under Rural field practice area. 2. To evaluate the factors influencing the health behavioral change in NCD patients. Methodology: This is a Cross-sectional study design conducted at Rural Health & Training Centre, Government Medical College, Ananthapuramu, from August 2023 to October 2023. Simple random sampling was used to select 150 registered NCD cases from the RHTC data-base. We included participants who were diagnosed with either diabetes, cardiovascular disease, chronic lung disease, or cancer after recruitment. Data were collected by using pre-designed semi-structured questionnaire. Data was analyzed using IBM SPSS version 25.0. Associations were tested using chi-squares and for all comparisons p-value <0.05 was considered significant. Results: In total 48 (32%) NCD cases have adopted suggested behavioral change instructed by the physician. Factors such as females, graduates, Class III & above SES, diagnosed between 5 to 10 years, not having any other co-morbidities were significantly associated with good health behavioral change. Conclusion: Around two third of the diagnosed NCD cases were not compliant to health behavioral change. Hence, health care providers need to provide behavioral change communication related to health behaviors in addition to standard medical care.